PENGARUH MATERI PEMBELAJARAN DIGITAL INTERAKTIF TERHADAP KREATIVITAS - Anugrah Budi Satria Mahardika; Mustaji Mustaji; Hari Sugiharto Setyaedhi (Akademika : Jurnal Teknologi Pendidikan, 2022)
The purpose of this study was to determine the effect of interactive teaching materials on students' creativity in learning the basics of graphic design. Students can use interactive teaching materials to support their creativity. This study uses an experimental type using a quasi-experimental design in the form of a nonequivalent control group design. This research was conducted at SMK Wijaya Putra Surabaya on the basics of graphic design involving 60 students of which 30 students were in the control class and 30 students in the experimental class. Pre and posttest sessions were conducted to obtain information about the impact of using interactive teaching materials on students' creativity. This research has implications for educators regarding the use of interactive digital learning materials for learning.